Interaction of a Plasmin A-Chain/t-PA B-Chain Hybrid Enzyme with Plasma Inhibitors In Vivo and In Vitro - Wilson, S; Chamberlain, P; Dodd, I; Esmail, A; Robinson, J H (Thrombosis and Haemostasis, 1990)
A hybrid plasminogen activator consisting of the “A” chain of plasmin linked to the “B” chain of rt-PA was inhibited in vitro in human and guinea pig plasmas 4 to 5-fold more rapidly than its parent activator, two-chain t-PA. Using zymographic and autoradiographic techniques together with the use of immunodepleted plasma the major inhibitor was identified as aIpha-2-antiplasmin. The pharmacokinetic profile of the hybrid in guinea pigs was determined by two different methods: disappearance of fibrinolytic activity and removal of radiolabelled hybrid from the circulation. Fibrinolytic activity was cleared rapidly via inhibitory mechanisms, whilst radiolabelled material was cleared considerably more slowly due to the formation of hybrid-inhibitor complexes. When the active site of the hybrid was reversibly acylated inhibitory mechanisms were evaded and a prolonged pharmacokinetic profile of activity was observed.